Rheological properties of epoxy resins in an shear ultrasonic field - PŁOWIEC, Ryszard (Archives of Acoustics, 1986)
Ultrasonic shear measurements were perfomed on epoxy resins: araldit F and epidian 5 in a temperature range from — 30 to 80°C and a frequency range from 10 to 800 MHz. Using reduced variables a "master curve", following the BEE model, was determined for K = 1.8 and 1.6, and 16 = 0.47 and 0.44, respectively. Both elasticity moduli and dynamic viscosity are given as frequency functions. It was found that Theological properties of both resins are close each other in an ultrasonic shear field.